Aberrations of the MRE11-RAD50-NBS1 DNA damage sensor complex in human breast cancer: MRE11 as a candidate familial cancer-predisposing gene - Bártková, Jiřina; Tommiska, J; Opluštilová, Lenka; Aaltonen, K; Tamminen, A; Heikkinen, T; Mistrik, Martin; Aittomaki, K; Blomqvist, C; Heikkila, P; Lukáš, Jiří; Nevanlinna, H; et al. (Molecular oncology, 2008)
The MRE11, RAD50, and NBS1 genes encode proteins of the MRE11-RAD50-NBS1 (MRN) complex critical for proper maintenance of genomic integrity and tumour suppression; however, the extent and impact of their cancer-predisposing defects, and potential clinical value remain to be determined. Here, we report that among a large series of approximately 1000 breast carcinomas, around 3%, 7% and 10% tumours showed aberrantly reduced protein expression for RAD50, MRE11 and NBS1, respectively. Such defects were more frequent among the ER/PR/ERBB2 triple-negative and higher-grade tumours, among familial (especially BRCA1/BRCA2-associated) rather than sporadic cases, and the NBS1 defects correlated with shorter patients' survival. The BRCA1-associated and ER/PR/ERBB2 triple-negative tumours also showed high incidence of constitutively active DNA damage signalling (gammaH2AX) and p53 aberrations. Sequencing the RAD50, MRE11 and NBS1 genes of 8 patients from non-BRCA1/2 breast cancer families whose tumours showed concomitant reduction/loss of all three MRN-complex proteins revealed two germline mutations in MRE11: a missense mutation R202G and a truncating mutation R633STOP (R633X). Gene transfer and protein analysis of cell culture models with mutant MRE11 implicated various destabilization patterns among the MRN complex proteins including NBS1, the abundance of which was restored by re-expression of wild-type MRE11. We propose that germline mutations qualify MRE11 as a novel candidate breast cancer susceptibility gene in a subset of non-BRCA1/2 families. Our data have implications for the concept of the DNA damage response as an intrinsic anti-cancer barrier, various components of which become inactivated during cancer progression and also represent the bulk of breast cancer susceptibility genes discovered to date.
Keywords: protein BRCA1; BRCA1 Protein; DNA Damage; nádory prsu; imunohistochemie; protein BRCA2; lidé; ženské pohlaví; DNA-Binding Proteins; Pedigree; Cell Cycle Proteins; genetická predispozice k nemoci; Breast Neoplasms; Female; zdraví rodiny; proteiny buněčného cyklu; zárodečné mutace; DNA vazebné proteiny; mutační analýza DNA; Family Health; BRCA2 Protein; Nuclear Proteins; enzymy opravy DNA; Mutant Proteins; poškození DNA; Genetic Predisposition to Disease; Germ-Line Mutation; Humans; Tumor Suppressor Protein p53; DNA Mutational Analysis; DNA Repair Enzymes; Immunohistochemistry